Implementasi Kebijakan Layanan Psikiatri Dalam Mengurangi Tingkat Stres Warga Binaan Pemasyarakatan (WBP) Kasus Penyalahgunaan Narkotika Di Lembaga Pemasyarakatan - Permana , Yoga Dwi Putra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Besides get stress from the effects of imprisonment, especially drug abuse prisoner cases, also get stress from a history of drug use before. The condition is likely to trigger a variety of deviation, so requiring special treatment. Therefore, it is necessary to have a policy that is technically a treatment in the form of services that can suppress and minimize prisoner stress levels and prevent the impact. The service is psychiatric. The research in this journal aims to describe the implementation of a policy of psychiatric services can reduce the stress level of drug abuse prisoner cases in Correctional Institution. The approach used is a post-positivism approach using library study techniques as data collection techniques. Data analysis techniques used are taxonomic analysis, that is, analysis that focuses attention on a particular domain that is very useful to describe phenomena or problems that are the target of the research. Based on the discussion and research carried out by the author, the results were obtained that the policy of psychiatric services can be implemented as an attempt to reduce the stress level of drug abuse prisoner cases in Correctional Institution. The author also recommends that psychiatric services can be organized in any correctional process in Correctional Institution throughout Indonesia in the following way: recommendation to the headquarters, in collaboration with the Local Regional Government/Local Government Hospital, and if necessary collaboration with organizations that active in the field of mental health and/ Faculty of Psychology or Medicine at local universities.